Study the Effect of Illumination Time Parameter of Diode Laser on Wound Healing Process - Dawood, Munqith S.; Salman, Saif Dawood (Nahrain University College of Engineering Journal, 2008)
In this study we introduce a solution for wound healing controlling therapy by using a monochromatic pulse diode laser light 650 nm, 50% duty cycle and 1 MHz. Many studies proved last years a positive effect of diode laser light application in wound healing process. In this paper we study the effect of time illumination parameter on healing process. For this kind of therapy, a 650 nm diode laser used. Its original electronic circuit drive was improved to give pulsed output laser of 50% duty cycle, 1 MHz. Twenty male mice, three months old were usd in this study (photo-biostimulation). The wound was made on bilateral back sides of each mouse, two sessions of illumination carried everyday for 12 and 18 minutes during 15 days time. This study was compared with our previous study set for 5 minutes for one session therapy in 1st and 2nd day of healing process.